Analysis of Factors Affecting Self-care of Type 2 Diabetes Mellitus Patients - Siwi Artini, Kusumaningtyas; Irawan AM, Ady (LPPM Universitas Duta Bangsa Surakarta, 2024)
Diabetes mellitus is a chronic disease characterized by increased blood sugar levels due to interference with insulin production or decreased sensitivity of insulin receptors in the body. Diabetes itself cannot be cured so it requires intensive treatment, especially proper self-care to support the patient's life. The aim of this study was to determine the factors that influence the self-caring of type 2 diabetes mellitus patients undergoing outpatient care at Dr. RSUD. Moewardi Surakarta. This research was carried out observationally with a cross-sectional design. Self-care measurement uses the Diabetes Self-care Management Questionnaire (DSMQ) instrument. The results of this study show that of the 167 responses involved, 131 respondents (78.4%) had good self-care and 36 respondents (21.6%) had poor self-care. Data analysis using chi-square showed that age, gender, education, marital status, employment and duration of DM had no effect on the patient's self-care (p>0.05).